PENGATURAN ASAS TANGGUNG JAWABAN MUTLLAK ATAS PENCEMARAN LIMBAH BAHAN BERBAHAYA DAN BERACUN OLEH KORPORASI - Fitri Fatma Wati (Dinamika, 2022)
ABSTRACTThe principle of strict liability in Article 88 of the UUPPLH which contains the phrase "without the need for proof of elements of error" has been changed in Article 22 number (33) of the Job Creation Law to "from its business and/or activities." Discussion on this research; A) How is the strict liability principle regulated in Article 88 UUPPLH and Article 22 number (33) of the Job Creation Act? B) How is the civil liability of corporations for B3 waste pollution related to the principle of strict liability? C) How is corporate criminal responsibility for B3 waste pollution related to the principle of strict liability? This research uses normative legal research methods. With the change in the phrase in Article 22 number (33) of the Job Creation Law, this responsibility is based on accountability by proving the element of error. Civil liability is based on the principle of strict liability, namely being responsible without the need to prove the element of guilt of the perpetrator as the basis for payment of compensation. Criminal liability is based on the principle of strict liability, namely the imposition of imprisonment or fines without questioning mistakes.Keyword : Stirict liability, Corporation, Pollution ABSTRAKAsas strict liability pada Pasal 88 UUPPLH yang terdapat frasa “tanpa perlu pembuktian unusur kesalahan” telah dirubah dalam Pasal 22 angka (33) UU Cipta Kerja menjadi “dari usaha dan/atau kegiatannya.” Pembahasan pada penelitian ini; A) Bagaimana pengaturan asas strict liability dalam Pasal 88 UUPPLH dan Pasal 22 angka (33) UU Cipta Kerja? B) Bagaimana pertanggungjawaban perdata korporasi atas pencemaran limbah B3 kaitannya dengan asas strict liability? C) Bagaimana pertanggungjawaban pidana korporasi atas pencemaran limbah B3 kaitannya dengan asas strict liability?. Penelitian ini menggunakan metode penelitian hukum normatif. Dengan perubahan frasa dalam Pasal 22 angka (33) UU Cipta Kerja telah menjadikan pertanggungjawaban tersebut berdasar pada pertanggungjawaban dengan membuktian unsur kesalahan. Pertanggungjawaban perdata berdasarkan asas strict liability yaitu bertanggung jawab tanpa perlu pembuktian unsur kesalahan si pelaku sebagai dasar pembayaran ganti kerugian. Pertanggungjawaban pidana berdasarkan asas strict liability yaitu pembebanan sanksi pidana penjara atau dan sanksi denda tanpa mempersolakan kesalahan.Kata Kunci: Stirict liability, Korporasi, Pencemaran